Cross-resistance of isoniazid, para-aminosalicylic acid and pasiniazid against isoniazid-resistant Mycobacterium tuberculosis isolates in China. (March 2020) - Li, Guilian; Zhang, Jingrui; Jiang, Yi; Zhao, Li-li; Liu, Haican; Li, Machao; Zhao, Xiuqin; Wan, Kanglin
Highlights: 84.6% (11/13) of p-aminosalicylic acid-resistant Mycobacterium tuberculosis isolates were susceptible to pasiniazid. 63 isoniazid (INH)-resistant isolates harboured mutations in the katG gene, inhA promoter or oxyR–ahpC intergenic region. 82.5% (52/63) of INH-resistant isolates with these mutations were susceptible to pasiniazid. 11 of 13 pasiniazid-resistant isolates carried mutations in katG, the inhA promoter or the oxyR – ahpC intergenic region. Abstract: Objectives: Pasiniazid is a chemical complex of isoniazid (INH) and para-aminosalicylic acid (PAS). The aim of this study was to explore the cross-resistance of INH, PAS and pasiniazid against INH-resistant Mycobacterium tuberculosis isolates in China. Methods: A Microplate alamarBlue® Assay was performed to determine the minimum inhibitory concentrations (MICs) of INH, PAS and pasiniazid against 109 INH-resistant M. tuberculosis isolates. A statistical analysis of the relationship between different genotypes, gene mutations, and INH, PAS or pasiniazid susceptibility was then performed. Results: Among the 109 INH-resistant isolates, 13 (11.9%) and 21 (19.3%) showed resistance to PAS and pasiniazid, respectively. Among the 13 PAS-resistant M. tuberculosis isolates, 11 remained susceptible to pasiniazid. Of 63 INH-resistant isolates harbouring mutations in katG, the inhA promoter or the oxyR – ahpC intergenic region, 52 remained susceptible to pasiniazid. Moreover, 11 of 13 pasiniazid-resistant isolates carried mutations in katG, the inhA promoter or the oxyR – ahpC intergenic region. Conclusion: Taken together, these results demonstrate that PAS resistance and mutations in the katG gene, inhA promoter or oxyR – ahpC intergenic region in INH-resistant M. tuberculosis have little effect on pasiniazid susceptibility.